Speed drive based on torque slip characteristic of the single phase induction motor - Auzani , Jidin; Jurifa , Mat Lazi; Fazli, Patkar; Aida Fazliana , Abdul Kadir; Mohd Ariff , Mat Hanafiah; Abdul Rahim , Abdullah (2006)
Most of the researches for adjustable speed drive focused on voltage amplitude control. However, its only control speed in the constraint limits. Adjustable frequency drives have not been widely used with single-phase induction motors. The scalar control law used for many three-phase inductions motor cannot be used in all operating regimes of the single-phase motor. Calculations show that the slip of the single-phase induction motor is not constant with changes in frequency at a constant load torque. A constant 'volts per hertz' law is found to give approximate rated torque over a portion of the upper speed range, but the maximum available torque decays rapidly below 50% of the base frequency. This paper aims to study the behavior of the single phase induction motor's torque and slip characteristic under variable frequency operation. By holding the level of magnetization constant, a control law can be achieved. This method is implemented for the practical adjustable speed of the single-phase induction motor. If time permit, the final draft paper includes the practical experimental results to compare the simulation results in order to achieve satisfactory agreement for torque and slip behavior of single-phase induction motors driven from variable frequency supplies